Impact of Perceived Barriers on Participation of Leisure Time Physical Activity among University Students - Ishaq, Ghulam; Rafique, Rafia (Journal of Pakistan Psychiatric Society, 2020)
Objective. The present study was intended to find the impact of perceived barriers in participation of leisure time physical activity. Design. The co-relational research design was employed to assess the hypothesis of the current study. Place and Duration of Study. This study was conducted at Institute of Applied Psychology, University of The Punjab. This study took 6 month for completion. Methods. Survey method was use to collect data for current study. Perceived barriers and leisure time physical questionnaire were use during survey. Result. The perceived barriers (lack of time, lack skills and lack of resources) predicted negatively leisure time physical activity which revealed that as perceived barriers (lack of time, lack skills and lack of resources) increase the level of leisure time physical activity decrease. Conclusion. This study also identified potential environmental and interpersonal barriers such as lack of time, resources and skills that prevent students from performing physical activity. These barriers will continue to prevent students from engaging in physical activity regardless of knowledge about its benefits. These findings provide useful information for future planning and implementation of physical activity interventions for students. Key words: perceived barriers, lack of time, skills, resources, physical activity